Low-power, deformable, dynamic multicolor electrochromic skin. (December 2020) - Koo, Jehyoung; Amoli, Vipin; Kim, So Young; Lee, Chaeyoung; Kim, Junho; Park, Sung-Min; Kim, Jeongsun; Ahn, Joon Mo; Jung, Kyung Jin; Kim, Do Hwan
Abstract: Active camouflage exhibited by certain creatures in nature such as cephalopods has inspired the fabrication of display devices for human-adaptive camouflage technologies. In order to realize that, electrochromic devices (ECDs) have attracted significant attention owing to their low-voltage operations and fast responses. However, the effective utilization of ECDs requires multicolor patterning, durable functioning, and wearable characteristics, simultaneously, but has not been explored. Here, we demonstrate a low-power, deformable, dynamic multicolor electrochromic skin (DMECS) that mimics the multicolor patterning and the active camouflage functionalities of the skins of cephalopods. The electrochromic polymers such as poly(3-hexylthiophene-2, 5-diyl), poly[2-methoxy-5-(2-ethylhexyl-oxy)-1, 4-phenylenevinylene], and P4a (green color polymer) are used to create purple, orange, and green colors, respectively. An iontronic polymer pump composed of an ionic liquid (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) incorporated in thermoplastic polyurethane is used as a deformable and transparent solid-state electrolyte that enables low-voltage (±3 V) operated DMECS with excellent cyclic coloration/bleaching stability (>35, 000 s), fast response (~1.75 s), and high durability under repeated 10, 000 cycles of compressive force (with a bending radius of 8 mm) and tensile strains (~100% up to 15, 000 s). We believe that our DMECS can offer user-controlled selective coloration/bleaching of arbitrary display patterns and open new avenues for next-generation wearable optoelectronics. Graphical abstract: Image 1 Highlights: A low-power, deformable, dynamic multicolor electrochromic skin (DMECS) inspired by the multicolor patterning and active camouflage ability of cephalopods skins is clearly described using electrochromic polymers and deformable, transparent iontronic polymer pumps. A novel iontronic polymer pump composed of an ionic liquid incorporated in thermoplastic polyurethane chains is used as a deformable and transparent elastomer electrolyte that enables low-power DMECS with excellent cyclic coloration/bleaching stability (>35, 000 s), fast response (~1.75 s), and high durability under repeated 10, 000 cycles of mechanical stimuli. Ultimately, the proposed strategy is expected to provide a new perspective for low-power artificial active camouflage and deformable multicolor wearable thin film displays.